Modified polytetrafluoroethylene resin composition and preparation method and application thereof
By modifying the polytetrafluoroethylene resin composition, the compatibility of polytetrafluoroethylene with polystyrene alcohol and inorganic fillers is improved, the cracking problem of the polytetrafluoroethylene composite film during the sintering process is solved, the thermal expansion coefficient and dielectric loss of the high-frequency copper clad plate are reduced, and the thermal stability of the laminate and the comprehensive performance of the copper clad plate are improved.
Patent Information
- Application Number
- CN202510096228.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-22
AI Technical Summary
In the prior art, the compatibility of polytetrafluoroethylene and inorganic fillers is poor, resulting in a high thermal expansion coefficient, and the polytetrafluoroethylene composite film is prone to cracking during sintering, affecting the comprehensive performance and yield of the copper clad plate.
Through click chemical reaction grafting mercaptosiloxane, silane modified alkenyl polyshenol was prepared, and the polytetrafluoroethylene powder activated by tert-butyl lithium was radically reacted with the silane modified alkenyl polyshenol to form the polyshenol modified polytetrafluoroethylene powder. The powder is dehydrated and condensed with the inorganic filler to produce a modified filler, which improves the compatibility of polytetrafluoroethylene with polysenol and inorganic filler, reduces the thermal expansion coefficient, and absorbs the volume shrinkage stress during the crystallization process of polytetrafluoroethylene by bonding polysenol during sintering to avoid cracking.
The compatibility of polytetrafluoroethylene with polystyrene alcohol and inorganic fillers is improved, the thermal expansion coefficient and dielectric loss of high-frequency copper clad plate is reduced, the thermal stability of the laminate is enhanced, the cracking problem of composite film is avoided, and the comprehensive performance and yield of copper clad plate is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of materials, and in particular to a modified polytetrafluoroethylene resin composition and a preparation method and application thereof. Background Art
[0002] The vehicle-mounted millimeter-wave radar is an important sensor for adaptive cruise control ACC, automatic braking system AEB, and forward collision warning FCW systems. With the rapid development of intelligent driving technology, the operating frequency band of vehicle-mounted millimeter-wave radar has developed from 24GHz to today's 77GHz, which puts forward more stringent requirements on high-frequency copper clad laminates. Polytetrafluoroethylene is currently the commercial resin with the lowest dielectric loss. Polytetrafluoroethylene high-frequency copper clad laminates are also the most commonly used substrate materials for 77GHz vehicle-mounted millimeter-wave radars and 6G communications. However, the thermal expansion coefficient of polytetrafluoroethylene reaches 120ppm / ℃, and inorganic fillers need to be added to reduce the thermal expansion coefficient; at the same time, the polytetrafluoroethylene high-frequency copper clad laminate reinforced with glass fiber cloth has a glass fiber cloth effect at microwave frequencies, resulting in phase difference, which affects the signal transmission accuracy of the radar.
[0003] Chinese patent CN110039851A discloses a method for preparing a polytetrafluoroethylene copper-clad laminate, wherein a mixture of polytetrafluoroethylene powder, lubricant, ceramic powder and short glass fiber is molded into a blank, and then copper foil is applied to the upper and lower surfaces after calendering to form a film, and a high-frequency copper-clad laminate is obtained by high-temperature lamination. This solution effectively avoids the glass fiber cloth effect, but polytetrafluoroethylene has poor compatibility with ceramic powder and weak intermolecular force, resulting in a high thermal expansion coefficient.
[0004] US Patent No. 6218015 discloses a casting mixture composed of dispersed granular fluorine-containing polymers, which is mixed with polytetrafluoroethylene and fillers and then cast into a film. The prepared copper-clad laminate has good dielectric properties and no glass fiber cloth effect. However, in this solution, polytetrafluoroethylene will shrink and crack during the film sintering process, affecting the comprehensive performance of the copper-clad laminate and reducing the yield rate.
[0005] In summary, the above existing technologies do not solve the problem of poor compatibility between inorganic fillers and polytetrafluoroethylene. The intermolecular force between the two is weak and the thermal expansion coefficient is high. At the same time, the polytetrafluoroethylene composite film still has the problem of cracking during the sintering process, which affects the comprehensive performance of the copper clad laminate and reduces the yield rate. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a modified polytetrafluoroethylene resin composition and its preparation method and application. The present invention can improve the compatibility of polytetrafluoroethylene and polyphenylene ether and the compatibility of polytetrafluoroethylene and inorganic fillers through a series of modification treatments, reduce the dielectric loss of inorganic fillers, improve the thermal stability of laminates, reduce the thermal expansion coefficient, and has great application value in the field of high-frequency copper clad laminates; at the same time, during sintering, the bonded polyphenylene ether can absorb the stress generated by the volume shrinkage during the crystallization process of polytetrafluoroethylene, which can solve the problem of cracking of polytetrafluoroethylene composite films.
[0007] The specific technical scheme of the present invention is:
[0008] In the first aspect, a modified polytetrafluoroethylene resin composition comprises the following raw materials in parts by weight: 10 to 25 parts of polyphenylene ether modified polytetrafluoroethylene powder, 40 to 60 parts of modified filler, and 70 to 100 parts of polytetrafluoroethylene emulsion. Among them:
[0009] The silane-modified alkenyl polyphenylene ether of the present invention is obtained by grafting mercaptosiloxane onto alkenyl polyphenylene ether through a click chemical reaction; the polyphenylene ether-modified polytetrafluoroethylene powder of the present invention is obtained by initiating a free radical reaction of the carbon-carbon double bonds of the silane-modified alkenyl polyphenylene ether by free radicals in the chain of polytetrafluoroethylene powder activated by tert-butyl lithium, which can realize chemical bonding of polytetrafluoroethylene with polyphenylene ether and siloxane groups. The modified filler of the present invention is obtained by hydrolyzing the siloxane in the polyphenylene ether-modified polytetrafluoroethylene powder and reacting it with the hydroxyl group of the inorganic filler through a dehydration condensation reaction, which can realize the modification of the inorganic filler.
[0010] The present invention can improve the compatibility of polytetrafluoroethylene and polyphenylene ether and the compatibility of polytetrafluoroethylene and inorganic filler through the above series of modification treatments, reduce the dielectric loss of inorganic filler, improve the thermal stability of high-frequency copper clad laminate, and reduce the thermal expansion coefficient; at the same time, during sintering, the bonded polyphenylene ether can absorb the stress generated by the volume shrinkage during the crystallization process of polytetrafluoroethylene, thereby solving the cracking problem of polytetrafluoroethylene composite film.
[0011] More preferably, the grafting rate of mercaptosiloxane in the silane-modified alkenyl polyphenylene ether is 2 to 5 wt %, wherein the grafting rate refers to the mass ratio of "grafted mercaptosiloxane" to "alkenyl polyphenylene ether".
[0012] In order to obtain better modification effects, it is necessary to regulate the grafting rate of mercaptosiloxane in silane-modified alkenyl polyphenylene ether. Specifically, if the grafting rate is too low, the siloxane is prone to insufficient contact with the inorganic filler during the subsequent modification process with the inorganic filler, resulting in poor modification effects. On the contrary, if the grafting rate is too high, the siloxane groups are prone to cross-linking after hydrolysis, affecting the interaction with the inorganic filler.
[0013] More preferably, the mass ratio of the polytetrafluoroethylene powder activated with tert-butyl lithium to the silane-modified alkenyl polyphenylene ether is 10:2-5.
[0014] In order to obtain a better modification effect, it is necessary to adjust the ratio of polytetrafluoroethylene powder activated by tert-butyl lithium and silane-modified alkenyl polyphenylene ether. The two react with free radicals to form polyphenylene ether-modified polytetrafluoroethylene powder. If the polyphenylene ether content is too low, it is insufficient to absorb the stress generated by volume shrinkage during PTFE crystallization, resulting in sintering cracking. On the contrary, if the polyphenylene ether content is too high, the overall temperature resistance of the material will be reduced, which is not conducive to the thermal stability of the laminate.
[0015] Preferably, the mercaptosiloxane includes one or more of γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane.
[0016] More preferably, the mass ratio of the polyphenylene ether modified polytetrafluoroethylene powder to the inorganic filler in the modified filler is 1:1-10.
[0017] In order to obtain better modification effect, it is necessary to limit the ratio of polyphenylene ether modified polytetrafluoroethylene powder to inorganic filler. Specifically: if the ratio of polyphenylene ether modified polytetrafluoroethylene powder is too low, the modification effect on the inorganic filler is poor, and the compatibility of the modified filler with polytetrafluoroethylene (emulsion part) is insufficient; if the ratio of polyphenylene ether modified polytetrafluoroethylene powder is too high, the dielectric constant of the modified filler is too low, which affects the control of the dielectric constant of the laminate by the filler.
[0018] Preferably, the solid content of the polytetrafluoroethylene emulsion is 50-70wt%.
[0019] Preferably, the inorganic filler is selected from one or more of silicon dioxide powder, titanium dioxide powder, silicon nitride powder, glass fiber, aluminum oxide powder and hollow glass microspheres.
[0020] Preferably, the modified polytetrafluoroethylene resin composition further comprises 0.5 to 1.5 parts of an emulsifier.
[0021] In a second aspect, the present invention provides a method for preparing the modified polytetrafluoroethylene resin composition, comprising the following steps:
[0022] 1) A silane-modified alkenyl polyphenyl ether is obtained by grafting mercaptosiloxane onto alkenyl polyphenyl ether through a click chemistry reaction; free radicals in the chain of polytetrafluoroethylene activated by tert-butyl lithium initiate a free radical reaction of the carbon-carbon double bonds of the silane-modified alkenyl polyphenyl ether to obtain polyphenyl ether modified polytetrafluoroethylene powder.
[0023] 2) The siloxane in the polytetrafluoroethylene powder is hydrolyzed and then reacted with the hydroxyl group of the inorganic filler to obtain a modified filler.
[0024] 3) Mixing and dispersing raw materials including polyphenylene ether modified polytetrafluoroethylene powder, modified filler and polytetrafluoroethylene emulsion to obtain a modified polytetrafluoroethylene resin composition.
[0025] Preferably, in step 1), the preparation method of the polyphenylene ether modified polytetrafluoroethylene powder specifically comprises: dissolving silane-modified alkenyl polyphenylene ether in a solvent under inert gas protection and anhydrous and oxygen-free atmosphere, adding polytetrafluoroethylene powder activated by tert-butyl lithium, heating and stirring to react, cooling, washing, and drying to obtain the polyphenylene ether modified polytetrafluoroethylene powder.
[0026] More preferably, in step 1), the solvent is toluene.
[0027] More preferably, in step 1), the temperature of the heating and stirring reaction is 80-85° C. and the time is 12-15 hours.
[0028] Preferably, in step 2), the preparation method of the modified filler specifically comprises: adding polyphenylene ether modified polytetrafluoroethylene powder to an ethanol aqueous solution and mixing evenly, adding an inorganic filler, heating to react, filtering, washing, and drying to obtain the modified filler.
[0029] More preferably, in step 2), the concentration of the ethanol aqueous solution is 80-85 wt %.
[0030] More preferably, in step 2), the uniform mixing is performed by ultrasonic mixing at room temperature for 30 to 45 minutes.
[0031] More preferably, in step 2), the heating reaction is carried out at a temperature of 72 to 75° C. and for a time of 16 to 19 hours.
[0032] In a third aspect, the present invention provides an application of the modified polytetrafluoroethylene resin composition in the preparation of a high-frequency copper-clad laminate, which specifically includes:
[0033] A) The modified polytetrafluoroethylene resin composition is uniformly coated on the surface of a substrate, sintered, and then peeled off to obtain a modified polytetrafluoroethylene dielectric film.
[0034] B) Copper foil is coated on the upper and lower surfaces of the modified polytetrafluoroethylene dielectric film, and hot pressed to obtain a laminate, namely a high-frequency copper-clad laminate.
[0035] Preferably, in step A), the substrate is a high temperature resistant glass sheet.
[0036] Preferably, in step A), the sintering temperature is 350-370° C. and the sintering time is 10-20 min.
[0037] Preferably, in step B), the hot pressing pressure is 5-8 MPa, the temperature is 340-380° C., and the time is 2-4 h.
[0038] Compared with the prior art, the beneficial effects of the present invention are:
[0039] (1) The present invention utilizes alkenyl polyphenyl ether and mercaptosiloxane to carry out thiol-ene click chemical reaction to obtain silane-modified alkenyl polyphenyl ether; and the carbon free radicals in the chain of polytetrafluoroethylene powder activated by tert-butyl lithium initiate the free radical reaction of carbon-carbon double bonds in silane-modified alkenyl polyphenyl ether, thereby achieving chemical bonding between polytetrafluoroethylene and polyphenyl ether and siloxane groups, improving the compatibility of polytetrafluoroethylene and polyphenyl ether, thereby improving the thermal stability of high-frequency copper clad laminates and reducing the thermal expansion coefficient; at the same time, during sintering, the bonded polyphenyl ether can absorb the stress generated by the volume shrinkage during the crystallization of polytetrafluoroethylene, thereby solving the problem of cracking of polytetrafluoroethylene composite films.
[0040] (2) The present invention achieves surface modification of the inorganic filler by allowing the siloxane groups of the polytetrafluoroethylene powder to undergo a dehydration condensation reaction with the hydroxyl groups of the inorganic filler after hydrolysis, thereby further reducing the dielectric loss of the inorganic filler; at the same time, the problems of poor compatibility between the inorganic filler and the polytetrafluoroethylene resin and weak intermolecular force are solved, further reducing the thermal expansion coefficient of the high-frequency copper clad laminate. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with the embodiments.
[0042] Overall embodiment
[0043] First, a modified polytetrafluoroethylene resin composition includes the following raw materials in parts by weight: 10 to 25 parts of polyphenylene ether modified polytetrafluoroethylene powder, 40 to 60 parts of modified filler, and 70 to 100 parts of polytetrafluoroethylene emulsion. Among them:
[0044] The polyphenylene ether modified polytetrafluoroethylene powder is obtained by initiating a free radical reaction of carbon-carbon double bonds of silane-modified alkenyl polyphenylene ether by free radicals in the chain of polytetrafluoroethylene powder activated by tert-butyl lithium. The silane-modified alkenyl polyphenylene ether is obtained by grafting mercaptosiloxane onto alkenyl polyphenylene ether through a click chemistry reaction. The modified filler is obtained by a dehydration condensation reaction of siloxane in the polyphenylene ether modified polytetrafluoroethylene powder with a hydroxyl group of an inorganic filler after hydrolysis.
[0045] In some preferred implementation cases, the grafting rate of mercaptosiloxane in the silane-modified alkenyl polyphenylene ether is 2-5 wt %.
[0046] In some preferred implementation cases, the mass ratio of the polytetrafluoroethylene powder activated with tert-butyl lithium to the silane-modified alkenyl polyphenylene ether is 10:2-5.
[0047] In some preferred implementation cases, the mercaptosiloxane includes one or more of γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane.
[0048] In some preferred implementation cases, the mass ratio of the polyphenylene ether modified polytetrafluoroethylene powder to the inorganic filler in the modified filler is 1:1-10.
[0049] In some preferred implementation cases, the solid content of the polytetrafluoroethylene emulsion is 50-70wt%.
[0050] In some preferred implementation cases, the inorganic filler is selected from one or more of silicon dioxide powder, titanium dioxide powder, silicon nitride powder, glass fiber, aluminum oxide powder and hollow glass microspheres.
[0051] In some preferred implementation cases, the modified polytetrafluoroethylene resin composition further includes 0.5 to 1.5 parts of an emulsifier.
[0052] Secondly, a method for preparing a modified polytetrafluoroethylene resin composition comprises the following steps:
[0053] 1) A silane-modified alkenyl polyphenyl ether is obtained by grafting mercaptosiloxane onto alkenyl polyphenyl ether through a click chemistry reaction; free radicals in the chain of polytetrafluoroethylene activated by tert-butyl lithium initiate a free radical reaction of the carbon-carbon double bonds of the silane-modified alkenyl polyphenyl ether to obtain polyphenyl ether modified polytetrafluoroethylene powder.
[0054] In some preferred implementation cases, in step 1), the preparation process of silane-modified alkenyl polyphenylene ether is as follows: toluene and alkenyl polyphenylene ether are added to a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, respectively, stirred to dissolve and heated to 80°C, mercaptosiloxane and peroxide initiator are added, and the temperature is lowered to room temperature after the reaction, and the obtained product is placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether.
[0055] In some more preferred implementation cases, the mass ratio of alkenyl polyphenylene ether to mercaptosiloxane is 10:0.5-1.5; the mass ratio of peroxide initiator to mercaptosiloxane is 1:35-70; and the reaction time is 10-15 hours.
[0056] In some preferred implementation cases, in step 1), the preparation method of the polyphenylene ether modified polytetrafluoroethylene powder specifically comprises: dissolving the silane-modified alkenyl polyphenylene ether in a solvent under the protection of an inert gas and an anhydrous and oxygen-free atmosphere, adding the polytetrafluoroethylene powder activated by tert-butyl lithium, heating and stirring to react, cooling, washing, and drying to obtain the polyphenylene ether modified polytetrafluoroethylene powder.
[0057] In some preferred implementation cases, in step 1), the specific process of activating the polytetrafluoroethylene powder with tert-butyl lithium is as follows: after the reaction bottle is flame-baked and nitrogen-exhausted three times, a mixed solution of tert-butyl lithium and triethylamine is added in an anhydrous, oxygen-free and nitrogen atmosphere, and polytetrafluoroethylene powder is added. After reacting at 0°C, the mixture is washed with THF and hexane at 0°C to obtain the polytetrafluoroethylene powder activated with tert-butyl lithium, and the powder is stored in a glass bottle in an anhydrous, oxygen-free and nitrogen atmosphere.
[0058] In some more preferred implementation cases, the molar ratio of tert-butyl lithium to triethylamine is 1:0.6-1.2; the mass ratio of polytetrafluoroethylene powder to tert-butyl lithium is 1:0.5-1; and the reaction time is 1.2-1.8 hours.
[0059] In some preferred implementation cases, in step 1), the solvent is toluene.
[0060] In some preferred implementation cases, in step 1), the temperature of the heating and stirring reaction is 80-85° C., and the time is 12-15 hours.
[0061] 2) The siloxane in the polytetrafluoroethylene powder modified by polyphenylene ether undergoes a dehydration condensation reaction with the hydroxyl group of the inorganic filler after hydrolysis to obtain a modified filler.
[0062] In some preferred implementation cases, in step 2), the preparation method of the modified filler specifically includes: adding polyphenylene ether modified polytetrafluoroethylene powder to an ethanol aqueous solution and mixing evenly, adding an inorganic filler, heating to react, filtering, washing, and drying to obtain the modified filler.
[0063] In some more preferred implementation cases, in step 2), the concentration of the ethanol aqueous solution is 80-85 wt %.
[0064] In some more preferred implementation cases, in step 2), the uniform mixing is performed by ultrasonic mixing at room temperature for 30 to 45 minutes.
[0065] In some more preferred implementation cases, in step 2), the heating reaction temperature is 72-75° C. and the time is 16-19 h.
[0066] 3) Mixing and dispersing raw materials including polyphenylene ether modified polytetrafluoroethylene powder, modified filler and polytetrafluoroethylene emulsion to obtain a modified polytetrafluoroethylene resin composition.
[0067] Finally, the present invention also provides the use of the modified polytetrafluoroethylene resin composition in the preparation of a high-frequency copper-clad laminate, which specifically includes:
[0068] A) The modified polytetrafluoroethylene resin composition is uniformly coated on the surface of a substrate, sintered, and then peeled off to obtain a modified polytetrafluoroethylene dielectric film.
[0069] In some preferred implementation cases, in step A), the substrate is a high temperature resistant glass sheet.
[0070] In some preferred implementation cases, in step A), the sintering temperature is 350-370° C., and the sintering time is 10-20 min.
[0071] B) Copper foil is coated on the upper and lower surfaces of the modified polytetrafluoroethylene dielectric film, and hot pressed to obtain a laminate, namely a high-frequency copper-clad laminate.
[0072] In some preferred implementation cases, in step B), the hot pressing pressure is 5-8 MPa, the temperature is 340-380° C., and the time is 2-4 h.
[0073] Specific examples and comparative examples.
[0074] The polytetrafluoroethylene emulsion used in the following cases of the present invention was purchased from Daikin Fluorine Chemical, with a brand name of D210C and a solid content of 60wt%; titanium dioxide was purchased from Suzhou Jinyi New Materials Technology Co., Ltd., with a particle size of 7.5μm; silicon dioxide was purchased from Yixin Mining Technology Co., Ltd., with a particle size of 5μm; alkenyl polyphenyl ether was purchased from Mitsubishi Gas, with a brand name of OPE-2st 2200; the emulsifier was fatty alcohol polyoxyethylene ether AEO-9, purchased from BASF; γ-mercaptopropyltrimethoxysilane was purchased from Beijing Inokai Technology Co., Ltd.
[0075] Preparation of polytetrafluoroethylene powder activated by tert-butyl lithium: After the reaction bottle was flame-baked and nitrogen-evacuated three times, a mixed solution of tert-butyl lithium and triethylamine in a molar ratio of 1:1 was added in an anhydrous, oxygen-free and nitrogen atmosphere, and 0.1 g of polytetrafluoroethylene powder (Zonyl MP1100, average particle size 4 μm) was added for every 1 mmol of tert-butyl lithium. After reacting at 0°C for 1.5 hours, the powder was washed with THF and hexane at 0°C to obtain polytetrafluoroethylene powder activated by tert-butyl lithium, which was stored in a glass bottle in an anhydrous, oxygen-free and nitrogen atmosphere.
[0076] Example 1
[0077] A modified polytetrafluoroethylene resin composition comprises, by weight, 20 parts of polyphenylene ether modified polytetrafluoroethylene powder, 50 parts of modified filler, 80 parts of polytetrafluoroethylene emulsion and 1 part of emulsifier (AEO-9).
[0078] The preparation method of polyphenylene ether modified polytetrafluoroethylene powder comprises the following steps:
[0079] (1) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 1000 g of toluene and 200 g of alkenyl polyphenylene ether were added respectively, the mixture was stirred to dissolve and the temperature was raised to 80°C, 20 g of γ-mercaptopropyltrimethoxysilane and 0.4 g of benzoyl peroxide were added, the mixture was reacted for 12 hours and then cooled to room temperature, the obtained product was placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether; the mercaptosilane grafting rate was calculated by weighing method to be 4wt%;
[0080] (2) Add 500 g of toluene and 40 g of silane-modified alkenyl polyphenylene ether to a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, stir to dissolve, add 100 g of polytetrafluoroethylene powder activated by tert-butyl lithium, stir and react at 80° C. for 13 hours, cool to room temperature, wash with toluene to remove unreacted silane-modified alkenyl polyphenylene ether, wash with ethanol, and dry to obtain polyphenylene ether-modified polytetrafluoroethylene powder; calculate the grafting rate of polyphenylene ether in the product by weighing method to be 10wt%;
[0081] The preparation method of the modified filler includes the following steps: adding 1 part of polyphenylene ether modified polytetrafluoroethylene powder to 85wt% ethanol aqueous solution, ultrasonically mixing at room temperature for 40 minutes, adding 5 parts of silicon dioxide, stirring at high speed at 73°C for 18 hours, filtering, washing and drying to obtain the modified filler.
[0082] Example 2
[0083] A modified polytetrafluoroethylene resin composition comprises, by weight, 20 parts of polyphenylene ether modified polytetrafluoroethylene powder, 50 parts of modified filler, 80 parts of polytetrafluoroethylene emulsion and 1 part of emulsifier (AEO-9).
[0084] The preparation method of polyphenylene ether modified polytetrafluoroethylene powder comprises the following steps:
[0085] (1) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 1000 g of toluene and 200 g of alkenyl polyphenylene ether were added respectively, the mixture was stirred to dissolve and the temperature was raised to 80°C, 12 g of γ-mercaptopropyltrimethoxysilane and 0.3 g of benzoyl peroxide were added, the mixture was reacted for 12 hours and then cooled to room temperature, the obtained product was placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether; the mercaptosilane grafting rate was calculated by weighing method to be 2 wt%;
[0086] (2) Add 500 g of toluene and 20 g of silane-modified alkenyl polyphenylene ether to a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, stir to dissolve, add 100 g of polytetrafluoroethylene powder activated by tert-butyl lithium, stir and react at 80° C. for 13 hours, cool to room temperature, wash with toluene to remove unreacted silane-modified alkenyl polyphenylene ether, wash with ethanol, and dry to obtain polyphenylene ether-modified polytetrafluoroethylene powder; calculate the grafting rate of polyphenylene ether in the product by weighing method to be 4.9wt%;
[0087] The preparation method of the modified filler includes the following steps: adding 1 part of polyphenylene ether modified polytetrafluoroethylene powder to 85wt% ethanol aqueous solution, ultrasonically mixing at room temperature for 40 minutes, adding 3.5 parts of silicon dioxide, stirring at high speed at 73°C for 18 hours, filtering, washing and drying to obtain the modified filler.
[0088] Example 3
[0089] A modified polytetrafluoroethylene resin composition comprises, by weight, 20 parts of polyphenylene ether modified polytetrafluoroethylene powder, 50 parts of modified filler, 80 parts of polytetrafluoroethylene emulsion and 1 part of emulsifier (AEO-9).
[0090] The preparation method of polyphenylene ether modified polytetrafluoroethylene powder comprises the following steps:
[0091] (1) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 1000 g of toluene and 200 g of alkenyl polyphenylene ether were added respectively, the mixture was stirred to dissolve and the temperature was raised to 80°C, 25 g of γ-mercaptopropyltrimethoxysilane and 0.4 g of benzoyl peroxide were added, the mixture was reacted for 12 hours and then cooled to room temperature, the obtained product was placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether; the mercaptosilane grafting rate was calculated by weighing method to be 5wt%;
[0092] (2) Add 500 g of toluene and 50 g of silane-modified alkenyl polyphenylene ether to a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, stir to dissolve, add 100 g of polytetrafluoroethylene powder activated by tert-butyl lithium, stir and react at 80° C. for 13 hours, cool to room temperature, wash with toluene to remove unreacted silane-modified alkenyl polyphenylene ether, wash with ethanol, and dry to obtain polyphenylene ether-modified polytetrafluoroethylene powder; calculate by weighing method that the grafting rate of polyphenylene ether in the product is 12wt%;
[0093] The preparation method of the modified filler includes the following steps: adding 1 part of polyphenylene ether modified polytetrafluoroethylene powder to 85wt% ethanol aqueous solution, ultrasonically mixing at room temperature for 40 minutes, adding 8 parts of silicon dioxide, stirring at high speed at 73°C for 18 hours, filtering, washing and drying to obtain the modified filler.
[0094] Example 4
[0095] A modified polytetrafluoroethylene resin composition comprises, by weight, 10 parts of polyphenylene ether modified polytetrafluoroethylene powder, 40 parts of modified filler, 70 parts of polytetrafluoroethylene emulsion and 1 part of emulsifier (AEO-9).
[0096] The preparation method of polyphenylene ether modified polytetrafluoroethylene powder comprises the following steps:
[0097] (1) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 1000 g of toluene and 200 g of alkenyl polyphenylene ether were added respectively, the mixture was stirred to dissolve and the temperature was raised to 80°C, 20 g of γ-mercaptopropyltrimethoxysilane and 0.4 g of benzoyl peroxide were added, the mixture was reacted for 12 hours and then cooled to room temperature, the obtained product was placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether; the mercaptosilane grafting rate was calculated by weighing method to be 4wt%;
[0098] (2) Add 500 g of toluene and 40 g of silane-modified alkenyl polyphenylene ether to a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, stir to dissolve, add 100 g of polytetrafluoroethylene powder activated by tert-butyl lithium, stir and react at 80° C. for 13 hours, cool to room temperature, wash with toluene to remove unreacted silane-modified alkenyl polyphenylene ether, wash with ethanol, and dry to obtain polyphenylene ether-modified polytetrafluoroethylene powder; calculate the grafting rate of polyphenylene ether in the product by weighing method to be 10wt%;
[0099] The preparation method of the modified filler includes the following steps: adding 1 part of polyphenylene ether modified polytetrafluoroethylene powder to 85wt% ethanol aqueous solution, ultrasonically mixing at room temperature for 40 minutes, adding 5 parts of silicon dioxide, stirring at high speed at 73°C for 18 hours, filtering, washing and drying to obtain the modified filler.
[0100] Example 5
[0101] A modified polytetrafluoroethylene resin composition comprises, by weight, 25 parts of polyphenylene ether modified polytetrafluoroethylene powder, 60 parts of modified filler, 100 parts of polytetrafluoroethylene emulsion and 1 part of emulsifier (AEO-9).
[0102] The preparation method of polyphenylene ether modified polytetrafluoroethylene powder comprises the following steps:
[0103] (1) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 1000 g of toluene and 200 g of alkenyl polyphenylene ether were added respectively, the mixture was stirred to dissolve and the temperature was raised to 80°C, 20 g of γ-mercaptopropyltrimethoxysilane and 0.4 g of benzoyl peroxide were added, the mixture was reacted for 12 hours and then cooled to room temperature, the obtained product was placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether; the mercaptosilane grafting rate was calculated by weighing method to be 4wt%;
[0104] (2) Add 500 g of toluene and 40 g of silane-modified alkenyl polyphenylene ether to a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, stir to dissolve, add 100 g of polytetrafluoroethylene powder activated by tert-butyl lithium, stir and react at 80° C. for 13 hours, cool to room temperature, wash with toluene to remove unreacted silane-modified alkenyl polyphenylene ether, wash with ethanol, and dry to obtain polyphenylene ether-modified polytetrafluoroethylene powder; calculate the grafting rate of polyphenylene ether in the product by weighing method to be 10wt%;
[0105] The preparation method of the modified filler includes the following steps: adding 1 part of polyphenylene ether modified polytetrafluoroethylene powder to 85wt% ethanol aqueous solution, ultrasonically mixing at room temperature for 40 minutes, adding 5 parts of silicon dioxide, stirring at high speed at 73°C for 18 hours, filtering, washing and drying to obtain the modified filler.
[0106] Example 6
[0107] A modified polytetrafluoroethylene resin composition comprises, by weight, 20 parts of polyphenylene ether modified polytetrafluoroethylene powder, 50 parts of modified filler, 100 parts of polytetrafluoroethylene emulsion and 1 part of emulsifier (AEO-9).
[0108] The preparation method of polyphenylene ether modified polytetrafluoroethylene powder comprises the following steps:
[0109] (1) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 1000 g of toluene and 200 g of alkenyl polyphenylene ether were added respectively, the mixture was stirred to dissolve and the temperature was raised to 80°C, 20 g of γ-mercaptopropyltrimethoxysilane and 0.4 g of benzoyl peroxide were added, the mixture was reacted for 12 hours and then cooled to room temperature, the obtained product was placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether; the mercaptosilane grafting rate was calculated by weighing method to be 4wt%;
[0110] (2) Add 500 g of toluene and 40 g of silane-modified alkenyl polyphenylene ether to a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, stir to dissolve, add 100 g of polytetrafluoroethylene powder activated by tert-butyl lithium, stir and react at 80° C. for 13 hours, cool to room temperature, wash with toluene to remove unreacted silane-modified alkenyl polyphenylene ether, wash with ethanol, and dry to obtain polyphenylene ether-modified polytetrafluoroethylene powder; calculate the grafting rate of polyphenylene ether in the product by weighing method to be 10wt%;
[0111] The preparation method of the modified filler includes the following steps: adding 1 part of polyphenylene ether modified polytetrafluoroethylene powder to 85wt% ethanol aqueous solution, ultrasonically mixing at room temperature for 40 minutes, adding 5 parts of silicon dioxide, stirring at high speed at 73°C for 18 hours, filtering, washing and drying to obtain the modified filler.
[0112] Example 7
[0113] A modified polytetrafluoroethylene resin composition comprises, by weight, 20 parts of polyphenylene ether modified polytetrafluoroethylene powder, 50 parts of modified filler, 80 parts of polytetrafluoroethylene emulsion and 1 part of emulsifier (AEO-9).
[0114] The preparation method of polyphenylene ether modified polytetrafluoroethylene powder comprises the following steps:
[0115] (1) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 1000 g of toluene and 200 g of alkenyl polyphenylene ether were added respectively, the mixture was stirred to dissolve and the temperature was raised to 80°C, 20 g of γ-mercaptopropyltrimethoxysilane and 0.4 g of benzoyl peroxide were added, the mixture was reacted for 12 hours and then cooled to room temperature, the obtained product was placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether; the mercaptosilane grafting rate was calculated by weighing method to be 4wt%;
[0116] (2) Add 500 g of toluene and 40 g of silane-modified alkenyl polyphenylene ether to a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, stir to dissolve, add 100 g of polytetrafluoroethylene powder activated by tert-butyl lithium, stir and react at 80° C. for 13 hours, cool to room temperature, wash with toluene to remove unreacted silane-modified alkenyl polyphenylene ether, wash with ethanol, and dry to obtain polyphenylene ether-modified polytetrafluoroethylene powder; calculate the grafting rate of polyphenylene ether in the product by weighing method to be 10wt%;
[0117] The preparation method of the modified filler includes the following steps: adding 1 part of polyphenylene ether modified polytetrafluoroethylene powder to 85wt% ethanol aqueous solution, ultrasonically mixing at room temperature for 40 minutes, then adding 2.5 parts of silicon dioxide and 2.5 parts of titanium dioxide, stirring at high speed at 73°C for 18 hours, filtering, washing and drying to obtain the modified filler.
[0118] Example 8
[0119] A modified polytetrafluoroethylene resin composition comprises, by weight, 20 parts of polyphenylene ether modified polytetrafluoroethylene powder, 50 parts of modified filler, 80 parts of polytetrafluoroethylene emulsion and 1 part of emulsifier (AEO-9).
[0120] The preparation method of polyphenylene ether modified polytetrafluoroethylene powder comprises the following steps:
[0121] (1) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 1000 g of toluene and 200 g of alkenyl polyphenylene ether were added respectively, the mixture was stirred to dissolve and the temperature was raised to 80°C, 20 g of γ-mercaptopropyltrimethoxysilane and 0.4 g of benzoyl peroxide were added, the mixture was reacted for 12 hours and then cooled to room temperature, the obtained product was placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether; the mercaptosilane grafting rate was calculated by weighing method to be 4wt%;
[0122] (2) Add 500 g of toluene and 40 g of silane-modified alkenyl polyphenylene ether to a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, stir to dissolve, add 100 g of polytetrafluoroethylene powder activated by tert-butyl lithium, stir and react at 80° C. for 13 hours, cool to room temperature, wash with toluene to remove unreacted silane-modified alkenyl polyphenylene ether, wash with ethanol, and dry to obtain polyphenylene ether-modified polytetrafluoroethylene powder; calculate the grafting rate of polyphenylene ether in the product by weighing method to be 10wt%;
[0123] The preparation method of the modified filler includes the following steps: adding 1 part of polyphenylene ether modified polytetrafluoroethylene powder to 85wt% ethanol aqueous solution, ultrasonically mixing at room temperature for 40 minutes, then adding 1.5 parts of silicon dioxide and 3.5 parts of titanium dioxide, stirring at high speed at 73°C for 18 hours, filtering, washing and drying to obtain the modified filler.
[0124] Comparative Example 1
[0125] A modified polytetrafluoroethylene resin composition comprises, by weight, 20 parts of a blended powder of polyphenylene ether (Sabic SA120) and polytetrafluoroethylene (Zonyl MP1100), 50 parts of a modified filler, 80 parts of a polytetrafluoroethylene emulsion, and 1 part of an emulsifier (AEO-9).
[0126] Among them, the mass ratio of polyphenylene ether to polytetrafluoroethylene is 4:10;
[0127] The preparation method of the modified filler includes the following steps: adding 1 part of a blended powder of polyphenylene ether and polytetrafluoroethylene to an 85wt% ethanol aqueous solution, ultrasonically mixing at room temperature for 40 minutes, adding 5 parts of silicon dioxide, stirring at high speed at 73°C for 18 hours, filtering, washing and drying to obtain the modified filler.
[0128] Comparative Example 2
[0129] A modified polytetrafluoroethylene resin composition comprises, by weight, 20 parts of polyphenylene ether modified polytetrafluoroethylene powder, 50 parts of silicon dioxide, 80 parts of polytetrafluoroethylene emulsion and 1 part of emulsifier (AEO-9).
[0130] The preparation method of polyphenylene ether modified polytetrafluoroethylene powder comprises the following steps:
[0131] (1) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 1000 g of toluene and 200 g of alkenyl polyphenylene ether were added respectively, the mixture was stirred to dissolve and the temperature was raised to 80°C, 20 g of γ-mercaptopropyltrimethoxysilane and 0.4 g of benzoyl peroxide were added, the mixture was reacted for 12 hours and then cooled to room temperature, the obtained product was placed in 5 times the volume of ethanol for precipitation, washed and dried to obtain silane-modified alkenyl polyphenylene ether; the mercaptosilane grafting rate was calculated by weighing method to be 4wt%;
[0132] (2) In a reaction bottle equipped with a condensing reflux device and a nitrogen atmosphere, 500 g of toluene and 40 g of silane-modified alkenyl polyphenylene ether were added and stirred to dissolve, and 100 g of polytetrafluoroethylene powder activated by tert-butyl lithium was added. After stirring and reacting at 80° C. for 13 hours, the mixture was cooled to room temperature and unreacted silane-modified alkenyl polyphenylene ether was washed with toluene. The powder was washed with ethanol and dried to obtain polyphenylene ether-modified polytetrafluoroethylene powder. The grafting rate of polyphenylene ether in the product was calculated by weighing method to be 10 wt%.
[0133] Application examples:
[0134] The modified polytetrafluoroethylene resin compositions in the above examples and comparative examples are used to prepare dielectric films and laminates for copper-clad laminates, respectively, and the preparation methods are as follows:
[0135] (1) Mixing various raw materials of the modified polytetrafluoroethylene resin composition according to a certain proportion and stirring them evenly to obtain a resin composition slurry;
[0136] (2) uniformly coating the resin composition slurry on a high temperature resistant glass sheet, sintering at 365° C. for 15 min, and obtaining a modified polytetrafluoroethylene dielectric film after peeling;
[0137] (3) Copper foil is coated on the upper and lower surfaces of the modified polytetrafluoroethylene dielectric film, and hot-pressed at a pressure of 6 MPa and 360° C. for 3 h to obtain the laminate, i.e., the high-frequency copper-clad laminate.
[0138] According to the IPC-TM650 test method, the dielectric constant, dielectric loss, and 288℃ thermal delamination time (T 288), and the Z-axis thermal expansion coefficient were tested, and the macroscopic cracking of the dielectric film was observed using a metallographic microscope. The results are shown in Table 1.
[0139] Table 1
[0140]
[0141] As can be seen from Table 1, the dielectric film obtained by using the modified polytetrafluoroethylene resin composition of the present invention in the sintering process in Examples 1 to 8 has no cracking, and the copper-clad laminate obtained by hot pressing the dielectric film has a dielectric loss of less than 0.001, has a low thermal expansion coefficient and excellent thermal stability, and is very suitable for high-frequency circuits, especially for applications in the field of millimeter waves; while in Comparative Example 1, polyphenylene ether and polytetrafluoroethylene are directly mixed, and the two are not chemically bonded, the inorganic filler is not effectively modified, and the dielectric film cracks during the sintering process. At the same time, the thermal expansion coefficient and thermal stability of the laminate are significantly deteriorated; in Comparative Example 2, the inorganic filler is not modified, and the dielectric loss and thermal expansion coefficient of the laminate are significantly increased. It can be seen that the method of the present invention is used to chemically bond polytetrafluoroethylene with polyphenylene ether and siloxane groups, and to modify the inorganic filler, which solves the cracking problem of the polytetrafluoroethylene composite dielectric film in the sintering process under the prior art, and reduces the thermal expansion coefficient of the polytetrafluoroethylene-based high-frequency copper-clad laminate.
[0142] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0143] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A modified polytetrafluoroethylene resin composition, characterized in that The invention comprises the following raw materials in parts by weight: 10 to 25 parts of polyphenylene ether modified polytetrafluoroethylene powder, 40 to 60 parts of modified filler, and 70 to 100 parts of polytetrafluoroethylene emulsion; The polyphenylene ether modified polytetrafluoroethylene powder is obtained by free radical reaction of carbon-carbon double bonds of silane modified alkenyl polyphenylene ether initiated by free radicals in the chain of polytetrafluoroethylene powder activated by tert-butyl lithium; The silane-modified alkenyl polyphenylene ether is obtained by grafting mercaptosiloxane onto alkenyl polyphenylene ether through a click chemical reaction; The modified filler is obtained by hydrolyzing siloxane in polyphenylene ether modified polytetrafluoroethylene powder and reacting it with hydroxyl groups of the inorganic filler through dehydration condensation reaction.
2. The modified polytetrafluoroethylene resin composition according to claim 1, characterized in that: The grafting rate of mercaptosiloxane in the silane-modified alkenyl polyphenylene ether is 2 to 5 wt %; The mass ratio of the polytetrafluoroethylene powder activated by tert-butyl lithium to the silane-modified alkenyl polyphenylene ether is 10:2-5.
3. The modified polytetrafluoroethylene resin composition according to claim 1 or 2, characterized in that: The mercaptosiloxane includes one or more of γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane; The solid content of the polytetrafluoroethylene emulsion is 50-70wt%.
4. The modified polytetrafluoroethylene resin composition according to claim 1, characterized in that: The mass ratio of the polyphenylene ether modified polytetrafluoroethylene powder to the inorganic filler in the modified filler is 1:1-10.
5. The modified polytetrafluoroethylene resin composition according to claim 1 or 4, characterized in that: The inorganic filler is selected from one or more of silicon dioxide powder, titanium dioxide powder, silicon nitride powder, glass fiber, aluminum oxide powder and hollow glass microspheres.
6. The modified polytetrafluoroethylene resin composition according to claim 1, characterized in that: It also includes 0.5 to 1.5 parts of emulsifier.
7. A method for preparing the modified polytetrafluoroethylene resin composition according to any one of claims 1 to 6, characterized in that include: 1) The alkenyl polyphenyl ether is grafted with mercaptosiloxane by click chemical reaction to obtain silane-modified alkenyl polyphenyl ether; the free radicals in the chain of polytetrafluoroethylene powder activated by tert-butyl lithium initiate the free radical reaction of the carbon-carbon double bonds of the silane-modified alkenyl polyphenyl ether to obtain polyphenyl ether-modified polytetrafluoroethylene powder; 2) The siloxane in the polytetrafluoroethylene powder modified by polyphenylene ether undergoes a dehydration condensation reaction with the hydroxyl group of the inorganic filler after hydrolysis to obtain a modified filler; 3) Mixing and dispersing raw materials including polyphenylene ether modified polytetrafluoroethylene powder, modified filler and polytetrafluoroethylene emulsion to obtain a modified polytetrafluoroethylene resin composition.
8. The preparation method according to claim 7, characterized in that: In step 1), the preparation method of the polyphenylene ether modified polytetrafluoroethylene powder specifically comprises: dissolving the silane modified alkenyl polyphenylene ether in a solvent under an inert gas and anhydrous and oxygen-free atmosphere, adding the polytetrafluoroethylene powder activated by tert-butyl lithium, heating and stirring to react, cooling, washing, and drying to obtain the polyphenylene ether modified polytetrafluoroethylene powder.
9. The preparation method according to claim 7, characterized in that: In step 2), the preparation method of the modified filler specifically comprises: adding polyphenylene ether modified polytetrafluoroethylene powder into an ethanol aqueous solution and mixing evenly, adding an inorganic filler, heating to react, filtering, washing, and drying to obtain the modified filler.
10. Use of the modified polytetrafluoroethylene resin composition according to any one of claims 1 to 6 or the modified polytetrafluoroethylene resin composition obtained by the preparation method according to any one of claims 7 to 9 in the preparation of high-frequency copper-clad laminates, characterized in that: A) coating the modified polytetrafluoroethylene resin composition on the surface of a substrate, sintering, and obtaining a modified polytetrafluoroethylene dielectric film after peeling; B) Copper foil is coated on the upper and lower surfaces of the modified polytetrafluoroethylene dielectric film, and hot pressed to obtain a laminate, namely a high-frequency copper-clad laminate.
Citation Information
Patent Citations
Preparation method of polytetrafluoroethylene copper-clad plate
CN110039851A
Casting mixtures comprising granular and dispersion fluoropolymers
US6218015B1
Thermosetting hydrocarbon polymer composition, and prepreg and thermosetting copper-clad plate prepared therefrom
CN110605880A
Printing ink scraper manufactured by lamination method and manufacturing method thereof
CN115157859A